Assessment of Bank Persero's Health Level Using The RGEC Method In 2018 - Dachlevie Riza; Iman Suriawinata; Muhammad Anhar (BPJP - STEI, 2021)
Public confidence in choosing a bank as a business partner based on health indicators Bank that existed at the bank. The research objective was to assess the soundness level of state-owned banks or HIMBARA, namely Bank Mandiri, Bank BNI'46, Bank Rakyat Indonesia and Bank Tabungan Negara using the RGEC method, namely the Risk Profile consisting of Net Performing Loans (NPL), Loan To Deposit (LDR), Good Corporate Governance (GCG), Earning namely Return on Assets (ROA), Net Interest Margin (NPM) and Adequacy Capital in 2018. the method’s research is descriptive research quantitative is a comparative research. The data used in this research is secondary data, the data is obtained from the 2018 annual reports of each of the state banks' websites. The results of the research on the assessment of the health level of the state-owned banks, the two state-owned banks had the same Composite Rating Percentage value, namely 90% (Bank Mandiri and Bank Rakyat Indonesia) and the BNI'46 Bank Composite Health Rating Percentage value was 93.33% while the Rating Percentage value State Savings Bank Composite Health is 73.33%. Researcher's Conclusion 3 (three) state- owned banks, namely Bank Mandiri, Bank BNI'46 and Bank BRI are in the Very Healthy category, while 1 (one) state- owned bank, namely Bank BTN, is in the Healthy category.